Changes in Resilience in Students of Occupational Therapy After Their First Exposure to Practice Placement Education - Rodríguez-Martínez, María Del Carmen; Toledano-González, Abel; Triviño-Juárez, José-Matías; Polonio-López, Begoña; Segura-Fragoso, Antonio; López-Martín, Olga; Cantero-Garlito, Pablo; Rodríguez-Hernández, Marta; Corregidor-Sánchez, Ana-Isabel; Romero-Ayuso, Dulce (Frontiers in Psychology, 2021)
Introduction: Resilience is a multidimensional and dynamic construct associated with positive growth and the capacity to transform stressful and negative factors into opportunities of personal development and self-improvement when faced with difficult experiences. The resilience process of each individual integrates multiple analysis levels, which range from genetic-environmental interactions to a complex process of adaptation between the individual and his/her family, friends, co-workers, society and culture. Objective: To determine whether resilience improves in students of occupational therapy when exposed for the first time to practice placement education. Methodology: Quasi-experimental, prospective, observational, multi-centre study with a sample composed of students from the Degree of Occupational Therapy of the public universities of XXX and XXX (Spain). Two weeks prior to the beginning of the practice education period, the participants completed a questionnaire that included sociodemographic data and the area of their internships. They were also given the Spanish version of the Connor-Davidson’s resilience scale (CD-RISC). All these instruments were also completed one week after the end of the clinical practice. Results: There were statistically significant differences between the variables that make up resilience and the different internship areas. On the other hand, there was a significant improvement of global resilience after the clinical practice period, in both women (13.85 points; p<0.001) and men (7.72 points; p<0.035), when the internship area was not considered. Conclusions: The results show that resilient students are more optimistic and work to improve a situation beyond doing simply what is expected of them, knowing how to control their feelings. This is beneficial for students in practice education, since, during these, they face difficult situations that require a resilient pattern, which helps reduce stress and the burnout syndrome.